Differences in Selected Performance Indicators Among Top Four Teams in Dubai Men’s World Rugby Sevens Series 2019/20 - Sulaiman, Norasrudin; Mohd Fauzi, Hanis Izzati; Cik Sofi, Mohd Shahkrul Nizam; Mohamad Ariffin, Mohamad Ridhwan (Environment-Behaviour Proceedings Journal, 2022)
The main objective of this investigation is to differentiate the performance of the four best teams in men’s rugby seven based on 13 performance indicators (Higham, Hopkins, Pyne, & Anson, 2014), Observational study (hand notational analysis) is performed to collect the data from the recorded video. Data were analyzed using SPSS (ver. 26) with a significant value set at pâ‰¤ 0.05. Based on the analysis, two PIs show a significant difference among the top four, and 11 PIs show vice versa results. Based on the data on PI’s, all top-four teams used different gameplay. The findings from this research may give some insight for rugby seven players and coaches to prepare for respective tournaments. Keywords: Performance Analysis, Performance Indicators, Rugby Seven eISSN: 2398-4287 Â© 2022. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open-access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under the responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians), and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v7iSI7.3821